Water Source Problems in Kulon Progo Yogyakarta in The Law Perspective - Kristanto PH; Yanti Fristikawati; Nugroho Adipradana (Research Collaboration Community (RCC), 2023)
Water is one of the important needs of society for everyday life, especially the need for clean water. To meet these needs, the community can get water from rivers, rainwater, and groundwater sources. Kulon Progo is one of the areas that are part of the Yogyakarta Province, where in Kulon Progo there are many water sources. However, based on research conducted, the water in Kulon Progo cannot be used as drinking water because it has been contaminated. For this reason, it is necessary to conduct a study, especially in terms of existing regulations, both national and regional regulations, whether these regulations can protect water sources so that they can protect the environment, including water sources. Indonesia already has rules regarding environmental protection and management, namely Law Number 32 of 2009, and regulations regarding Water Resources, namely Law Number 17 of 2019. From these regulations, it can be said that they have been able to protect water sources so that they are not polluted, but awareness and the need for community participation are not carried out activities that can cause water pollution.